Analysis of student interest in choosing manual methods and computer applications in linear programming courses - Depriwana Rahmi; Annisa Kurniati; Andie Tangonan Capinding; Mohamad Firdaus Ahmad; Suci Yuniati (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
The rapid development of information technology has had a significant impact on education, including in the teaching of linear programming courses. Lecturers are required to teach both manual and computer-based application methods. However, the level of student interest in both methods remains unclear, necessitating a more in-depth analysis. This study employed a quantitative descriptive approach using a survey technique, in which the questionnaire was developed around five main indicators: ease of understanding the steps, perceived time efficiency, confidence in the final result, personal preference in solving problems, and perceived challenges or obstacles. Respondents consisted of 31 fourth-semester Mathematics Education students who had taken the Linear Programming course. The analysis indicates that software such as POM-QM for Windows and AtoZmath is more efficient and time-saving for solving linear programming problems. A total of 74.2% of students strongly agreed that these applications are more time-efficient. Students tend to prefer these tools because they enable automatic calculations that yield optimal solutions and minimize the risk of manual computation errors, thereby increasing confidence in the accuracy of the results. However, manual methods remain essential, as they promote students’ conceptual understanding, particularly in model formulation and constraint identification. Moreover, this approach strengthens mathematical reasoning and logical thinking skills, which serve as a fundamental basis for problem-solving before utilizing technological assistance. Therefore, both methods are important to teach in the classroom due to their respective advantages.